Florida Consumer Preferences for Ornamental Landscape Plants - Hayk Khachatryan; Alicia Rihn (EDIS)
Certain attributes of ornamental landscape plants make them more attractive to consumers. This 5-page fact sheet assesses the impacts of price, plant type, pollinator friendliness, production methods, and origin attributes on consumers’ purchasing likelihood for ornamental landscape plants. Recommendations for green industry stakeholders are also provided. Written by Hayk Khachatryan and Alicia Rihn, and published by the UF Department of Food and Resource Economics, October 2016.